PENYIDIKAN TINDAK PIDANA SKIMMING DALAM TRANSAKSI ELEKTRONIK OLEH KEPOLISIAN DAERAH SULAWESI SELATAN: INVESTIGATION OF THE CRIME OF SKIMMING IN ELECTRONIC TRANSACTIONS BY SOUTH SULAWESI REGIONAL POLICE - Rahma Indah, Nur; Haris Hamid, Abd.; Zubaidah, Siti (Clavia, 2021)
This study aims to determine 1) the process of investigating the Crime of Skimming at the South Sulawesi Police. 2) the obstacles faced by the South Sulawesi Regional Police in dealing with the Crime of Skimming. This research was conducted at the Indonesian National Police for the South Sulawesi Region, BNI KLN Ratulangi Makassar and the Financial Services Authority Regional Office 6 Makassar. The research method used is an empirical juridical approach. The results of the study indicate that 1) Skimming is included in the crime of information and electronic transactions which prohibits anyone intentionally and without rights or against the law accessing computers and or electronic systems in any way with the aim of obtaining electronic information and or electronic documents as regulated in Article 30 paragraph (2) of Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions or hereinafter referred to as the ITE Law. This skimming crime mode can occur by placing the skimmer (scan tool) at the mouth of the ATM card entry and using a small camera to record the victim's ATM PIN. This skimmer is used to retrieve the data on the ATM card and then it will be copied to a fake ATM card or a blank card. 2) Obstacles faced by investigators in carrying out investigations against the crime of skimming the first are Internal factors, including Human Resources, facilities and infrastructure, the second is External Factors, including the lack of public understanding about the dangers of skimming crime, Factors perpetrators and banks are less intensive in maintaining every ATM.